Analytical and theoretical aspects of the influence of IT technologies in the context of optimization of the organization of construction processes - BYLOV, Yuriy; ANIN, Viktor (Ways to Improve Construction Efficiency, 2025)
The main purpose of this article is to study the analytical and theoretical aspects of the impact of IT technologies on the optimization of the organization of construction processes. The theoretical foundations and practical aspects of the use of information technologies to optimize organizational processes in construction are investigated. In particular, this study focuses on the analysis of opportunities and advantages provided by IT technologies to improve the coordination of work, resource management, planning and control over the implementation of construction projects. The prospects for the use of IT technologies in construction are substantiated, which contributes to the optimization of organizational processes, improving interaction between project participants and reducing the risks of errors. Automation of planning and resource management allows you to reduce costs and increase the efficiency of management decisions. Thanks to such technologies, greater transparency, quality control and safety are ensured. Therefore, the possibilities and practical application of modern IT technologies in the construction industry are relevant and necessary. It allows not only to assess their impact on the efficiency and quality of work, but also contributes to the formation of new approaches to the implementation of construction projects in the context of global technological changes. The specifics of organizational processes require a significant revision of the concepts and operating principles of optimization models of construction production. The study focuses on the development and formalization of a digital platform for algorithmic-criterion modeling of parametric optimization of organizational processes in construction. The proposed approach is aimed at systematizing and improving the mechanisms of coordination of intersectoral interaction, which contributes to the effective use of the material and technical base of the domestic market. The proposed concept is based on analytical, theoretical and methodological approaches to the systematization of a complex multicomponent system, using a digital platform that ensures consistency between project time indicators, material flows and cost parameters, as well as contributes to the automation of organizational and technological processes and the introduction of intelligent resource monitoring systems